DETERMINANTS OF STIGMA ON PEOPLE LIVING WITH HIV AND AIDS IN INDONESIA (EVIDENCE FROM 2017 IDHS DATA) - Mohammad Taufiq Adiansyah; Andrei Ramani; Ni'mal Baroya (The Indonesian Journal of Public Health, 2023)
Introduction: People living with human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) face bio-psycho-socio-spiritual problems. The stigma against PLWHA exists in more than 65 countries. Indonesia occupied the highest position in the Pacific with a case rate of 62.8%. Stigma has contributed to the failure of HIV and AIDS epidemic-control programs. Aims: To determine the stigma against PLWHA in Indonesia. Method: This study used the 2017 IDHS dataset with a cross-sectional design. The study sample comprised 47.233 people. The variables studied included age, sex, marital status, educational level, economic status, employment status, mass media exposure, type of residence, knowledge about HIV and AIDS, and stigma against PLWHA. The data analysis technique was the chi-square test and logistic regression with α 0.05 (5%). Result: Factors that determined the stigma of PLWHA include age 15-19 (OR 1.611), age 20-24 (OR 1.438), age 25-29 (OR 1.131), age 30-34 (OR 0.993), male gender (OR 0.834), married status (OR 1.416), educational level less (1.247), very poor economic status (OR 1.503), poor (OR, 1.134), medium (OR 1.080), rich (OR 0.972), not working ( OR 1.065), and lack of knowledge (OR 2.588). Conclusion:  person aged 15-24 years, female, single, have low education, poorest/poor, do ot have a job, and have a low level of knowledge about HIV and AIDS are very likely to be stigmatized towards PLWHA. Education related to HIV and AIDS, especially how HIV and AIDS are transmitted, still needs to be improved so that it can reach all levels in society